2020
DOI: 10.3389/fonc.2020.592853
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Anti-Tumor Mechanisms of Coumarins

Abstract: Coumarins are a class of compound with benzopyrone as their basic structure. Due to abundant sources, easy synthesis, and various pharmacological activities, coumarins have attracted extensive attention from researchers. In particular, coumarins have very significant anti-tumor abilities and a variety of anti-tumor mechanisms, including inhibition of carbonic anhydrase, targeting PI3K/Akt/mTOR signaling pathways, inducing cell apoptosis protein activation, inhibition of tumor multidrug resistance, inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 49 publications
1
87
0
Order By: Relevance
“…In particular, coumarin derivatives have shown a variety of biological activities such as CK2 inhibitors 39 , EGFR 40 , PI3K-AKT-mTOR signalling inhibitors 41–43 . Furthermore, their anticancer potential, tumour targets, diverse mechanisms of action as well as their advantages and disadvantages have been recently reviewed 44 . In continuation with our previous work and prompted by these considerations, to further explore the influences of structural modifications on the coumarin and psoralene core on the activity and selectivity towards membrane-bound hCA isozyme, we have designed and synthesised a small library of methyl-2-[4-methyl-2-oxo-7–(2-oxo-2-arylethoxy)-8-propylchromen-3-yl]acetate and 2–(5-methyl-7-oxo-3-aryl-9-propyl-7H-furo[3,2-g]chromen-6-yl)acetic acid derivatives were a propyl group in the position 8 or 9 has been introduced compared to the previously synthesised derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, coumarin derivatives have shown a variety of biological activities such as CK2 inhibitors 39 , EGFR 40 , PI3K-AKT-mTOR signalling inhibitors 41–43 . Furthermore, their anticancer potential, tumour targets, diverse mechanisms of action as well as their advantages and disadvantages have been recently reviewed 44 . In continuation with our previous work and prompted by these considerations, to further explore the influences of structural modifications on the coumarin and psoralene core on the activity and selectivity towards membrane-bound hCA isozyme, we have designed and synthesised a small library of methyl-2-[4-methyl-2-oxo-7–(2-oxo-2-arylethoxy)-8-propylchromen-3-yl]acetate and 2–(5-methyl-7-oxo-3-aryl-9-propyl-7H-furo[3,2-g]chromen-6-yl)acetic acid derivatives were a propyl group in the position 8 or 9 has been introduced compared to the previously synthesised derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins and their derivatives have been regarded as an important family of anticancer lead compounds, which exhibit diverse effects such as anti-proliferation, antiinvasion, anti-metastasis, anti-angiogenesis and inducing apoptosis. The various mechanisms of their anticancer action have been widely explored [22][23][24][25][26][27][28], including inhibition of carbonic anhydrase, PI3K/AKT/mTOR signaling pathway, microtubule polymerization, monocarboxylate transporters, hypoxia-inducible factor-1, acting on apoptosis proteins, inhibiting tumor multidrug resistance, and regulating ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the data demonstrated that LCT-3d induced gastric cell apoptosis through DR5-mediated mitochondrial pathway. The activation of Caspase family proteins is an important event leading to cell apoptosis (21). At the early stage of apoptosis, Caspase 3 and Caspase 9 were activated, and they served as biomarker proteins of apoptosis (22).…”
Section: Discussionmentioning
confidence: 99%